Jacobi methods on some fuzzy linear systems - Nurhakimah Ab Rahman (Fakulti Sains dan Teknologi, 2012)
Linear systems are widely used in many fields of science and engineering. There are some applications which involve linear systems. However, majority of the parameters of the system are represented by fuzzy rather than crisp numbers. Therefore it is important to perform numerical algorithms that would treat general fuzzy linear systems for solving them.